2022
DOI: 10.3390/jcm11112956
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes following Biologically Enhanced Demineralized Bone Matrix Augmentation of Complex Rotator Cuff Repair

Abstract: Complex rotator cuff tears provide a significant challenge for treating surgeons, given their high failure rate following repair and the associated morbidity. The purpose of this study is to evaluate the clinical outcomes of patients who underwent biologically enhanced demineralized bone matrix augmentation of rotator cuff repairs. Twenty patients with complex rotator cuff tears underwent arthroscopic rotator cuff repair by a single surgeon with demineralized bone matrix (DBM) augmentation that was biologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…Sie berichten über Kombinationen von dermalen Allografts mit subakromialer Bursa, platelet-rich plasma (PRP) und platelet-poor plasma (PPP), konzentriertem Knochenmarkaspirat, und autologem Thrombin. Bisher konnte noch kein substanzieller klinischer Benefit dieser Verfahren gezeigt werden [6,52,78].…”
Section: » Jede Therapieentscheidung Ist Individuell Zu Fällenunclassified
“…Sie berichten über Kombinationen von dermalen Allografts mit subakromialer Bursa, platelet-rich plasma (PRP) und platelet-poor plasma (PPP), konzentriertem Knochenmarkaspirat, und autologem Thrombin. Bisher konnte noch kein substanzieller klinischer Benefit dieser Verfahren gezeigt werden [6,52,78].…”
Section: » Jede Therapieentscheidung Ist Individuell Zu Fällenunclassified
“…Li et al conducted a review of the current literature and reported that bone quality, insertion depth, insertion angle, size of rotator cuff tear, preoperative corticosteroid injections, anchor design, and the materials used to produce anchors may influence the anchor pullout strength, leading to a poor recovery [1]. Regarding massive rotator cuff tear that cannot be fixed directly, Wellington et al used a biologically enhanced demineralized bone matrix for the augmentation and found that 10 of 20 patients who received this treatment still suffered from a retear at follow-up [2]. This outcome suggested that there is still a long way to go to enhance the repair of rotator cuff.…”
mentioning
confidence: 99%